Disorders of Sex Development An Integrated Approach to Management - Hutson, John M.; Hutson, John M.; Warne, Garry L.; Warne, Garry L.; Grover, Sonia R.; Grover, Sonia R. (Springer Berlin Heidelberg : Imprint: Springer, 2012)
The birth of a baby with ambiguous genitalia triggers a chain reaction of difficulties that rapidly spread to the entire family and most medical attendants, leading to lasting effects on the gender identity, personality, and sexual functioning of the unfortunate individual.  The rapid advances in medicine over the last 50 years have totally changed the outlook for children with disorders of sex development (DSD), but there is still much to learn.   This book crystallizes the combined experience of a leading dedicated unit over 25 years in delivering expert medical and surgical care to children with DSD in a holistic environment.  It documents the most recent advances in the molecular biology and embryology of sex development, and describes each disorder in detail.  The clinical presentation and approach to diagnosis are described both for babies and for children presenting later in childhood or at adolescence.  The chapters on management highlight all the latest knowledge and include the shared wisdom of the authors on current controversies, such as the timing of surgical treatment.  Finally, the authors describe their short-, medium-, and long-term outcomes, which demonstrate the strengths of holistic team management.